Intra-mitochondrial self-assembly to overcome the intracellular enzymatic degradation of l-peptides. Issue 46 (6th May 2020) - Jeena, M. T.; Lee, Seokyoung; Barui, Ayan Kumar; Jin, Seongeon; Cho, Yuri; Hwang, Suk-Won; Kim, Sehoon; Ryu, Ja-Hyoung
Abstract : The design of peptide-based therapeutics is generally based on the replacement of l -amino acids with d -isomers to obtain improved therapeutic efficiency. Abstract : The design of peptide-based therapeutics is generally based on the replacement of l -amino acids with d -isomers to obtain improved therapeutic efficiency. However, d -isomers are expensive and frequently induce undesirable immune responses. In the present work, we demonstrate that an intra-mitochondrially self-assembling amphiphilic peptide exhibits analogous activity in both d - and l -isomeric forms. This outcome is in contrast to the general observation considering higher therapeutic efficiencies of d -isomers compared with l -analogues. This suggests that l -peptides overcome proteolytic degradation during intra-mitochondrial self-assembly both in vitro and in vivo .